2001
DOI: 10.1111/j.1526-4629.2001.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Clams and Data Involving local communities in monitoring can lead to conservation success in all sorts of unanticipated ways: A case in Fiji

Abstract: Early one morning, a small group of Fijian villagers gathers on the beach. In front of them are the mudflats, mangroves, and coral reefs that make up their qoliqoli-their traditional community-owned fishing grounds that have sustained their village for generations. From a distance, they look just like other groups in the past that have gone out to harvest resources. But this group is carrying compasses, tape measures, metal quadrat frames, and clipboards. They are not going fishing. Instead, they are harvestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 0 publications
1
26
1
1
Order By: Relevance
“…After three and a quarter years of management, clams had increased in abundance by 13 times in the closed areas and by five times in the fished area. Catch per unit effort increased and people reported catching clams twice as quickly as before the closure [20,59]. Data collected in 2002 show that, after five years of protection, there have been further increases in clam abundance.…”
Section: Box 2 Success For Large-scale Closures In Atlantic Fishing mentioning
confidence: 99%
See 2 more Smart Citations
“…After three and a quarter years of management, clams had increased in abundance by 13 times in the closed areas and by five times in the fished area. Catch per unit effort increased and people reported catching clams twice as quickly as before the closure [20,59]. Data collected in 2002 show that, after five years of protection, there have been further increases in clam abundance.…”
Section: Box 2 Success For Large-scale Closures In Atlantic Fishing mentioning
confidence: 99%
“…In response to the effects that they were observing, and aware of the temptation for fishers seeking other species to take clams from the closed area, the community decided to make the area completely no-take. The success of the Ucunivanua project for fisheries replenishment, and the high level of community involvement have led to similar projects developing throughout Fiji [20,59]. Communities are returning to their traditional practice of tabuor closed areas, combining centuries of local knowledge with the latest developments in marine ecology.…”
Section: Box 2 Success For Large-scale Closures In Atlantic Fishing mentioning
confidence: 99%
See 1 more Smart Citation
“…At the center of this debate is the suggestion that larvae from highly productive populations in marine reserves may move outside reserves and enhance populations in harvested areas (7,8). A few studies have demonstrated spatial and/or temporal patterns of recruitment or abundance that suggest larvae exported from reserves can enhance nearby fished populations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the larval export effect remains controversial (3), in part because empirical evidence remains limited (6).…”
mentioning
confidence: 99%
“…A previous record found that the tabu tradition had been practiced in areas of Kumi fishing boundaries (Tawake et al, 2001). In this study, we found that knowledge on the tabu tradition was shared among Kumi villagers, and perceptions on its importance for the community served as the bases for collective actions of fisheries resource management (including the LMMA and sea cucumber restoration).…”
Section: Perceptions Rooted In Traditional Institutionsmentioning
confidence: 57%